The use of blogs to improve formal letter writing skill among IKM Lumut students / Norliza Zainal - Zainal, Norliza (2015)
Blogging is viewed as a tool in helping the students to improve their formal letter writing skill through a self-correction practice and autonomous learning behavior (Arana, 2013). To ascertain such contention, this study aims to investigate the use of blogs to improve students’ formal letter writing skill. Two classes or a total of 30 students from Institut Kemahiran MARA Lumut participated in this study that ran for 6 weeks. A quasi experimental research design was used to answer the research questions in this study. These two classes were introduced to blogging as they wrote job application letters in their blogs during the 6-week treatment. A pre-test and post-test were administered one week before and after the treatment was carried out. The results of the pre-test were compared with the result of the post-test to identify the improvement of their writing skills. After the experiment, the students were asked to express their attitude towards using blogs in learning through questionnaire and interview. The findings reveal that students’ formal letter writing skill improved based on the results of independent sample t-test and paired samples t-test of their pre-test and post-test mean scores at p<0.05 level of significance. Furthermore, two raters unanimously agree that students’ job application letter writing improved on content, format and mechanics. The result from questionnaire also indicated that students had positive attitudes in the overall attitude (M= 4.53) of learning writing through blog. The interview responses implied that blogging can be considered as an effective platform in facilitating the development of students’ formal letter writing skill. Therefore, it can be concluded that blogging can help in improving students’ formal letter writing skill in ESL classroom.